2012
DOI: 10.1111/j.1365-2141.2012.09027.x
|View full text |Cite
|
Sign up to set email alerts
|

Burkitt lymphoma in UGANDA, the legacy of Denis Burkitt and an update on the disease status

Abstract: Burkitt lymphoma (BL) was first described in Uganda in 1958 as a sarcoma of the jaw but later confirmed to be a distinct form of Non Hodgkin lymphoma (NHL). This discovery was the defining moment of cancer research in Uganda, which eventually led to the establishment of a dedicated cancer research institute, the Uganda Cancer Institute (UCI) in 1967. The centre was dedicated to Denis Burkitt in recognition of his contribution to cancer research in East Africa. BL is still the commonest NHL in childhood in Ugan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 17 publications
0
20
0
1
Order By: Relevance
“…Some of these findings are similar to the findings from a previous study in Sudan where lymphoma, leukemia, and Wilms' tumors were reported to be the three most common cancers in this age group 25 and similar pattern has been seen in North African countries such as Tunisia 26 and Morocco 27 . The Khartoum childhood cancer profile is different from that in neighboring sub-Saharan African countries, which were mostly dominated by Burkett lymphoma and Kaposi sarcoma 28 .…”
Section: Discussionmentioning
confidence: 78%
“…Some of these findings are similar to the findings from a previous study in Sudan where lymphoma, leukemia, and Wilms' tumors were reported to be the three most common cancers in this age group 25 and similar pattern has been seen in North African countries such as Tunisia 26 and Morocco 27 . The Khartoum childhood cancer profile is different from that in neighboring sub-Saharan African countries, which were mostly dominated by Burkett lymphoma and Kaposi sarcoma 28 .…”
Section: Discussionmentioning
confidence: 78%
“…Burkitt lymphoma (BL) is the commonest childhood cancer in many African countries, with an incidence between 5 and 10/100 000. [1][2][3][4][5] Burkitt and colleagues pioneered curative therapy at the Uganda Cancer Institute (UCI) in the 1950s. [6][7][8] In subsequent years, survival of all children with endemic BL (eBL) at the UCI has been reported between 30% and 65%, consistent with recent reports from Kenya and Malawi.…”
Section: Introductionmentioning
confidence: 99%
“…Altogether there were 52 reports that appeared to comply with the inclusion criteria, some sets of reports were considered under Criterion A and were eliminated including: Emmaneul B et al [31], Fleming A [32], Molyneux, Elizabeth M et al [33], Orem J et al [34], Walusansa et al [35] .…”
Section: Resultsmentioning
confidence: 99%